Numerical Simulation on the Penetration Behavior of the Projectile during the Water Injection Stage of Water-Projectile-Assisted Injection Molding Process - Tangqing Kuang; Qiang Feng; Tian Liu; Luohao Zhong; Yanqing Wang; Hesheng Liu (Advances in Polymer Technology)
Water-projectile-assisted injection molding (W-PAIM) is a novel molding process for plastic pipes with complicated shape. It utilizes high-pressure water as a power to push a solid projectile to penetrate through the melt to form a hollow space. In order to investigate the penetration behavior of the projectile during the water injection stage of W-PAIM process, numerical simulation of the water injection stage of a W-PAIM pipe with straight and curved segments was carried out. A turbulent flow for the driving water was considered in the motion equation, and the dynamic mesh technology was used to deal with the moving solid projectile. The simulation results, including RWT and the flow fields, were compared with those of water-assisted injection molding (WAIM) pipe with the same outer dimensions. It was found that the residual wall thickness (RWT) of the W-PAIM pipe is much thinner than that of the WAIM pipe. The projectile has a crucial influence on the RWT. The pressure fields of W-PAIM and WAIM are very similar in both straight and curved segments. The velocity field and strain rate field near the penetration front in W-PAIM are quite different from those in WAIM due to the drag flow caused by the projectile penetration.